A formação inicial de professores nas humanidades: reflexões didáticas - Judite Carecho (Investigação, 2019)
This work is divided into four sections discussing topics relating to the teaching of Geography, History, Modern Languages and Portuguese (language and literature), respectively. The volume brings together eighteen chapters of teaching teachers, researchers, trainee teachers and professionalized teachers, associated with the Faculty of Arts and Humanities of the University of Coimbra. More than finding revenue for teachers in initial training, it is intended to raise the debate and provide a space for reflection on themes central to the teaching of humanities.